Effectiveness of luseogliflozin over conventional therapy on liver fibrosis, disease activity and metabolic attributes in patients with metabolic associated fatty liver disease and type ii diabetes mellitus: an open-label randomized controlled trial - Mazri, Mohamad Syamil (2023)
Background Metabolic Associated Fatty Liver Disease (MAFLD) is a new term that describes a spectrum of liver disease with its causative metabolic factors comprising obesity, type 2 diabetes mellitus (T2DM), and metabolic syndrome. To this day, there is no definitive treatment for this condition. This study aimed to ascertain the effectiveness of luseogliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor on liver fibrosis and metabolic attributes in patients with MAFLD and T2DM. Method This is a prospective, open-label, randomized controlled study involving patients diagnosed with MAFLD and T2DM. Subjects were randomly allocated into two groups, either the control group who received standard pharmacological T2DM treatment without any SGLT2 inhibitor or active group who received oral luseogliflozin 5mg daily for 3 months. Measurement of Fibrosis-4 Index score (Fib-4) to determine fibrosis and blood tests including liver enzymes, HbA1C and cholesterol level to determine liver and metabolic attributes were recorded at baseline and 3 months post intervention. Results There were 58 patients randomized in this study and the results showed statistically significant differences in the reduction of Fib-4 index between the two groups after 3 months. Fib-4 index in active group reduced from 2.24  0.77 to 1.57  0.75 vs control group from 2.41  1.58 to 2.86  2.26, p <0.001. Between group analysis for Fib-4 index shown significant difference between the two group. Luseogliflozin was also observed to improved HbA1C (-1.22  1.36%, p<0.001), AST (-11.59  13.41U/L, p = 0.003), total Cholesterol (-0.4  0.78mmol/L, p=0.002), and triglyceride (-0.19  0.63mmol/L, p= 0.024) levels after 3 months of study as compared to baseline. Conclusion Compared to controls, addition of luseogliflozin had shown to be effective in improving liver fibrosis, liver disease activity, glycemic control, and lipid parameters in MAFLD with T2DM.